Primary leiomyosarcoma originating from the azygos vein misdiagnosed as tracheal tumor: a case report and literature review - Zhu, Long-fei; Wang, Yu-jun; Zuo, Chun-jian; Deng, Yuan-lin; Jiang, Bin (Frontiers in Oncology, 2025)
Leiomyosarcomas are uncommon mesenchymal neoplasms. Primary mediastinal leiomyosarcomas are even rarer with only a limited number of cases reported. Given the high potential for recurrence and metastasis, accurate and timely diagnosis become extremely crucial for treatment. Herein, we present a unique case of a 70-year-old asymptomatic male patient with a primary leiomyosarcoma originating from the azygos vein, which was misdiagnosed as a tracheal tumor preoperatively. This report highlights the critical importance of including leiomyosarcoma in the differential diagnosis of mediastinal masses, especially when preoperative pathological findings indicate a spindle cell neoplasm of smooth muscle origin. Early recognition can more effectively assess intraoperative risks, optimize the surgical plan, and are essential to prevent locally invasive growth and potential metastasis. By analyzing the specific case and reviewing relevant literature, this study seeks to enhance our understanding of the diagnosis and treatment of primary mediastinal leiomyosarcoma, derive insights from our clinical experience, and emphasize the importance of maintaining suspicion and prudence among healthcare professionals.